The Symbolism in KFC: A Semiotic Analysis of Branding Through Peirce’s Theory (PANOPTICON: Journal of English Studies, 2025)
In the competitive fast-food industry, KFC's logo and slogan play a crucial role in brand identity and customer perception. This study examines the image of Colonel Sanders in the logo and the tagline, "It's Finger Lickin' Good," through Charles Sanders Peirce's semiotic theory. The analysis explores how these verbal and visual elements engage customers and create meaning. Using qualitative methods such as customer perception surveys, content analysis, and literature reviews, the study finds that the tagline enhances the brand's sensory appeal, while the logo fosters trust and nostalgia. Together, these elements build an emotional connection that boosts customer engagement and brand loyalty. The study highlights the importance of semiotic analysis in understanding branding strategies in the fast-food industry. Applying Peirce's concepts of representamen, interpretant, and object, the research illustrates how KFC effectively navigates brand communication challenges to establish itself as a globally recognized fast-food brand. These findings contribute to ongoing discussions in semiotics, branding, and marketing, offering insights for future research in these areas.